Research-action tools to reinterpret school inclusion concept - Beatrice Chirio; Reza Nabibakhsh (University of Bologna, 2022)
This article explores the research-action tools used for a Linguistic Inclusion path, performed at some primary and first level secondary schools in Turin during the school year. The authors allocate these instruments to a multi-disciplinary framework of anthropological, sociological and pedagogic concepts, such as Bonetti's Relational Learning, Ward's Education and Anarchism and Dolci's Maieutic Method. From these, three categories arise: participation, collaboration and care tools. These latter carry two main objectives: to investigate the dynamics of the three macro-areas within the contexts in which they are used, and at the same time to take action on them, through the co-creation of new educational possibilities.